The IPL 60+ Program : a singular case of senior education in an intergenerational context - Faria, Susana (2015)
Aiming for the promotion of active aging, the IPL60+ Senior Education Program is designed for adults over 50 years old and is part of the Polytechnic Institute of Leiria Strategic Plan since 2008, allowing its enrolled members to attend Curricular Units from any of the IPL’s graduation courses. Therefore, the Program is conceived as an intergenerational senior education initiative. Its mission is to help change the aging paradigm through the stimulation and promotion of formative, educational and socio-cultural activities that involve the individuals in their own learning path and lifelong development, always in an intergenerational sociability context able to strengthen mutual learning processes. By enrolling in regular classes, senior students share school premises with the younger students, being able to benefit from all the IPL Campus’ services and spaces including classrooms, as well as canteens, cafeterias and libraries. In parallel, the IPL60+ Program has been striving to complement the academic component, diversifying the offer of intellectual and physically stimulating activities that are appropriate to this specific audience. Simultaneously, there is a constant appeal to personal intervention and initiative, valuing the students’ cooperation in the organization of a series of their own initiatives, some with a clearly educational tone, others more recreational. Demand has been increasing substantially, expanding from 17 students enrolled in 2008 to 111 in the 2nd semester of 2010/11.